2020
DOI: 10.1007/s00167-020-06179-y
|View full text |Cite
|
Sign up to set email alerts
|

Widening of the popliteal hiatus on sagittal MRI view plays a critical role in the mechanical signs of discoid lateral meniscus

Abstract: PurposeThis study was undertaken to elucidate the clinical significance of widening of the popliteal hiatus on magnetic resonance imaging (MRI) after a torn discoid lateral meniscus (DLM). MethodsIncluded are 125 knees with meniscal disorders after arthroscopic surgery, divided according to preoperative MRI and symptoms into group A (torn DLM with mechanical symptoms,11 knees); group B (torn DLM without mechanical symptoms,41 knees); group C (asymptomatic DLM, 19 knees); and group D (medial meniscal tears, 54 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Discoid lateral meniscus (DLM) of knee joint is a fibrous cartilage with abnormal morphology and structure 1 , divided into complete, incomplete and Wrisberg 2 , affecting 0.4%-5% Western population and >16% Asian population 3 , which is symptomized by pain, swelling, snapping, buckling and locking 4 , seriously impacting the patients' quality of life.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Discoid lateral meniscus (DLM) of knee joint is a fibrous cartilage with abnormal morphology and structure 1 , divided into complete, incomplete and Wrisberg 2 , affecting 0.4%-5% Western population and >16% Asian population 3 , which is symptomized by pain, swelling, snapping, buckling and locking 4 , seriously impacting the patients' quality of life.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Previous studies have reported that many radiographic parameters, including a widened lateral joint line, cupping of the lateral tibial plateau, squaring of the lateral femoral condyle, an elevated fibular head and a condylar cut-off sign, are useful and convenient for DLM screening [2,[7][8][9][10][11][12]. Arthroscopic visualization and MRI parameters are also utilized in DLM screening [6,[21][22][23]. All these parameters originate from the hypoplasia of the lateral tibial plateau and the lateral femoral condyle related to DLM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that many radiographic parameters, including a widened lateral joint line, cupping of the lateral tibial plateau, squaring of the lateral femoral condyle, an elevated bular head and a condylar cut-off sign, are useful and convenient for DLM screening [2,[5][6][7][8][9][10]. Arthroscopic visualization and MRI parameters are also utilized in DLM screening [4,[14][15][16]. All these parameters originate from the hypoplasia of the lateral tibial plateau and the lateral femoral condyle related to DLM.…”
Section: Discussionmentioning
confidence: 99%